Den billedlige vending - Mitchell, W.J.T. (Passage - Tidsskrift for litteratur og kritik, 2012)
W.J.T. Mitchell: "Den billedlige vending" Abstract W.J.T. Mitchell: “The Pictorial Turn” Taking as a point of departure Richard Rorty’s idea of the history of philosophy as a series of “turns”, Mitchell’s essay from 1992 argues that the so-called ‘linguistic turn’, predominant in the 20th century, has been superseded by a ‘pictorial turn’. The essay thus, in Mitchells own words, “looks at the way modern thought has reoriented itself around visual paradigms that seem to threathen and overwhelm any possibility of discursive mastery.” Analysing theories by e.g. Panofsky and Althusser, the essay “looks at pictures ‘in theory’ – and at theory in itself as a form of picturing”.